The Challenges of Translating Jane Austen’s Irony: Samples from 150 Years of Norwegian Versions of the Novels - Marie Nedregotten Sørbø (Humanities, 2022)
Irony is often perceived to be an inherent quality of Jane Austen’s narrative voice and attitude, but is it translatable? It has been argued that Austen should ‘stay at home’, since foreign versions tend to alter her novels in various ways. However, her novels are nevertheless translated into more languages, giving her a more global presence than ever before. What kind of Austen is received in these versions? Does she still have a sharp eye for human peculiarities and wry comments on the vagaries of romance? The study of Austen in translation is still in its early phase, with most languages yet to be investigated. This article will focus on Norwegian translations between 1871 and the present time. They include serials for newspapers and journals, paperbacks for the popular market, as well as handsome classic author editions. The challenge of understanding and transmitting Austen’s irony cuts across such genres and channels of publication and is always a prominent issue when studying them. In this article, I will choose some examples of narrative irony from the novels and compare them to several translated versions (in back-translation). They serve as illustrations of what is at stake, but also, implicitly, as demonstrations of Austen’s own peculiar voice and authorial qualities.